2007
DOI: 10.1016/j.ddmec.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sphingosine 1 phosphate receptor type 1 receptors in acute kidney injury

Abstract: Sphingosine 1-phosphate analogs have a multitude of effects with the best characterized one being mediated through sphingosine 1-phosphate type 1 receptors (S1P1 receptor). Currently, S1P1 receptor agonists are being developed and tested for human disease. Because of the potent effect of S1P1 agonists to modulate the immune system, these compounds are ideal for blocking immune mechanisms that mediate acute kidney injury (AKI). This disorder continues to remain an important disease that is characterized by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…). These findings suggest that FTY720 has beneficial effects and is able to reduce the progression of the disease toward chronic tubulointerstitial fibrosis and renal insufficiency through its ability to deplete lymphocytes and stop the inflammatory reactions (Okusa and Lynch ; Peters et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). These findings suggest that FTY720 has beneficial effects and is able to reduce the progression of the disease toward chronic tubulointerstitial fibrosis and renal insufficiency through its ability to deplete lymphocytes and stop the inflammatory reactions (Okusa and Lynch ; Peters et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the in vitro and in vivo findings of the effects of fibrosis suggested that S1P is involved in fibrosis. Renal fibrosis has been shown to occur through inflammatory pathways involving S1PR1 (Okusa and Lynch 2007 ). In this study, the direct effects of S1P on renal fibrosis and not those mediated by inflammation were examined in a nude mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of receptors involved in AKI-mediated injury include the FAS receptor and TGFb receptor. 40,41 Examples of receptors involved in epithelial cytoprotection and repair include the EGF receptor, 42 HGF receptor (c-Met), 43 sphingosine-1-phosphate receptor, 44 and netrin-1 receptor. 45 Many questions relating to the role of receptors in AKI remain unanswered, including the sources of the putative ligands, mechanisms of receptor activation, and signaling pathways involved in protection from injury or involved with epithelial repair.…”
Section: Receptorsmentioning
confidence: 99%
“…Both AKI and CKD, especially at the end--stages, have shown an alarming increase for the past 30 years in the US and worldwide. 62,63 Many kidney diseases have primary or secondary vascular lesions, which can be accelerated by risk factors, such as hypertension, diabetes and obesity. 63 Generation of new vessels in the kidney is not confined to embryonic development but is also a mechanism activated in response to disease.…”
Section: Vascular Development and Kidney Diseasesmentioning
confidence: 99%